Effectiveness of a Function-Based ABA Intervention for Tantrum Reduction in a Preschool Child: A Single-Subject Design Study - Anis, Durriya; Kausar, Erum; Fatima, Insia (Annals of Human and Social Sciences, 2025)
This study aimed to explore the effectiveness of a function-based Applied Behavior Analysis (ABA) intervention using Differential Reinforcement of Alternate Behavior (DRA) and Extinction to reduce the temper tantrums in a preschool-aged child living in a Pakistani joint family. Temper tantrums in pre-school years, if left unaddressed, lead to behavioral problems in later life (Hoyniak et al., 2022). It was hypothesized: The intervention would significantly reduce tantrum’s mean rate compared to baseline and tantrum behavior would be replaced with functionally equivalent adaptive behaviors. A single-subject A-B-A withdrawal design was employed for at 30 days intervention guided by Functional Behavioral Assessment (FBA). Quantitative frequency recordings were conducted during baseline, intervention, and follow up phases. The results showed significant reduction in temper tantrums frequency with results being maintained in the follow ups. Future studies should utilize the intervention on larger population and incorporate caregiver fidelity checks to generilze and maintain the integrity of the intervention